2017
DOI: 10.1159/000460298
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda Made It Clearer: A Review of 542 Patients in a Single Institution

Abstract: Background: It is essential to interpret fine needle aspiration biopsy (FNAB) material correctly to create a common language among pathologists and surgeons, leading to a uniform approach to thyroid nodule management. We aimed to compare FNAB reports of patients at our institution who were treated with total thyroidectomy, before and after the Bethesda classification system. Patients and Methods: Patients who underwent total thyroidectomy for thyroid nodules are reviewed. 226 patients who underwent total thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Some of the tools that could prove effective in predicting malignancy in TN assessment include the assessment of the TN size, thyroid-stimulating hormone (TSH) level at the time of diagnosis, Bethesda System for Reporting Thyroid Cytopathology (BSRTC) and Thyroid Imaging Reporting and Data System (TI-RADS). 11 , 12 Consequently, establishing a concordance between the diagnostic procedures (fine-needle aspiration [FNA] and US) might reduce the health care costs as well as numbers of nonessential procedures in the population at risk could be reduced. Findings from various researches also reported that the FNA biopsy must be interpreted precisely to generate a common language among pathologists and surgeons, to enable them to establish a uniform TN management strategy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the tools that could prove effective in predicting malignancy in TN assessment include the assessment of the TN size, thyroid-stimulating hormone (TSH) level at the time of diagnosis, Bethesda System for Reporting Thyroid Cytopathology (BSRTC) and Thyroid Imaging Reporting and Data System (TI-RADS). 11 , 12 Consequently, establishing a concordance between the diagnostic procedures (fine-needle aspiration [FNA] and US) might reduce the health care costs as well as numbers of nonessential procedures in the population at risk could be reduced. Findings from various researches also reported that the FNA biopsy must be interpreted precisely to generate a common language among pathologists and surgeons, to enable them to establish a uniform TN management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from various researches also reported that the FNA biopsy must be interpreted precisely to generate a common language among pathologists and surgeons, to enable them to establish a uniform TN management strategy. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Acar et al suggested in their paper, the Bethesda system allows for more accurate predictions for suspicious and malignant lesions (11). Although this is true, the rates of malignancy of indeterminate lesions vary, and the factors that can predict the risks of malignancy of indeterminate nodules to avoid unnecessary thyroidectomies are being investigated (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need to establish a uniform classification system that would provide clear-cut thresholds for management and reduce inter-observer variability. This study attempts to compare the Pap classification system [15] with the Bethesda 2014 system [20] as well as to determine the accuracy of the Bethesda system in predicting the oral potentially malignant disorders (OPMD) and malignant cases so as to allow us to establish its clinical applicability.…”
Section: Introductionmentioning
confidence: 99%